Nebulized Bacteriophage in a Patient With Refractory Mycobacterium abscessus Lung Disease. (12th April 2022) - Dedrick, Rebekah M; Freeman, Krista G; Nguyen, Jan A; Bahadirli-Talbott, Asli; Cardin, Mitchell E; Cristinziano, Madison; Smith, Bailey E; Jeong, Soowan; Ignatius, Elisa H; Lin, Cheng Ting; Cohen, Keira A; Hatfull, Graham F
Abstract: An elderly man with refractory Mycobacterium abscessus lung disease previously developed anti-phage neutralizing antibodies while receiving intravenous phage therapy. Subsequent phage nebulization resulted in transient weight gain, decreased C-reactive protein, and reduced Mycobacterium burden. Weak sputum neutralization may have limited the outcomes, but phage resistance was not a contributing factor.